Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
x+\(\dfrac{3}{15}=\dfrac{1}{3}\)
<=>\(x=\dfrac{1}{3}-\dfrac{3}{15}\)
<=>x=\(\dfrac{5}{15}-\dfrac{3}{15}\)
<=>x=\(\dfrac{2}{15}\)
Vậy S={\(\dfrac{2}{15}\)}
\(-5\left(x+\dfrac{1}{5}\right)-\dfrac{1}{2}\left(x-\dfrac{2}{3}\right)=\dfrac{3}{2}x-\dfrac{5}{6}\)
<=>\(-5x-1-\dfrac{1}{2}x+\dfrac{1}{3}=\dfrac{3}{2}x-\dfrac{5}{6}\)
<=>\(-\dfrac{11}{2}x-\dfrac{3}{2}x=-\dfrac{5}{6}+1-\dfrac{1}{3}\)
<=>-7x=\(-\dfrac{1}{6}\)
<=>x=\(\dfrac{7}{6}\)
Vậy S={\(\dfrac{7}{6}\)}
\(x\cdot6\dfrac{2}{7}+\dfrac{3}{7}\cdot2\dfrac{1}{5}-\dfrac{3}{7}=-2\)
<=>\(x\cdot\dfrac{44}{7}+\dfrac{3}{7}\cdot\dfrac{11}{5}-\dfrac{3}{7}=-2\)
<=>\(x\cdot\dfrac{44}{7}+\dfrac{3}{7}\cdot\left(\dfrac{11}{5}-1\right)=-2\)
<=>\(x\cdot\dfrac{44}{7}+\dfrac{3}{7}\cdot\dfrac{6}{5}=-2\)
<=>\(\dfrac{44}{7}x\)\(+\dfrac{18}{35}=-2\)
<=>\(\dfrac{44}{7}x=-2-\dfrac{18}{35}\)
<=>\(\dfrac{44}{7}x=-\dfrac{88}{35}\)
<=>x=\(-\dfrac{88}{35}\cdot\dfrac{7}{44}\)
<=>x=\(-\dfrac{2}{5}\)
Vậy S={\(-\dfrac{2}{5}\)}
a, \(\left|2x+1\right|=3\)
=> 2x + 1 = 3 hoặc 2x + 1 = -3
=> 2x = 3 - 1 hoặc 2x = -3 - 1
=> 2x = 2 hoặc 2x = -4
=> x = 1 hoặc x = -2
b, \(2\frac{1}{2}x+1\frac{1}{2}=2\frac{2}{3}\)
=> \(\frac{5}{2}x+\frac{3}{2}=\frac{8}{3}\)
=> \(\frac{5}{2}x=\frac{8}{3}-\frac{3}{2}\)
=> \(\frac{5}{2}x=\frac{16-9}{6}\)
=> \(\frac{5}{2}x=\frac{7}{6}\)
=> \(x=\frac{7}{6}:\frac{5}{2}=\frac{7}{6}\cdot\frac{2}{5}=\frac{7}{3}\cdot\frac{1}{5}=\frac{7}{15}\)
c, \(3\cdot5^{x-3}+1=16\)
=> 3 . 5x-3 = 16 - 1
=> 3 . 5x-3 = 15
=> 5x-3 = 15 : 3
=> 5x-3 = 5
=> x - 3 = 5 : 5
=> x - 3 = 1
=> x = 1 + 3 = 4
d, \((x-1)^2=25\)
=> \((x-1)^2=5^2\)
=> x - 1 = 5 hoặc x - 1 = -5
=> x = 6 hoặc x = -4
e, \((-2)^2+\left|3x+1\right|=(-28)\cdot7\)
=> 4 + |3x + 1| = -196
=> |3x + 1| = -196 - 4 = -200
=> |3x + 1| = -200
Không thỏa mãn điều kiện
Bài giải:
Câu 1: a, \(\left(-2\right).4.5.38.\left(-25\right)\)
\(=\left[\left(-2\right).5\right].\left[4.\left(-25\right)\right].38\)
\(=\left(-10\right).\left(-100\right).38\)
\(=1000.38=38000\)
b,\(\frac{1}{3}+\frac{3}{8}-\frac{7}{12}\)
\(=\left(\frac{1}{3}+\frac{3}{8}\right)-\frac{7}{12}\)
\(=\frac{17}{24}-\frac{7}{12}=\frac{1}{8}\)
c, \(\frac{-5}{8}.\frac{5}{12}+\frac{-5}{8}.\frac{7}{12}+2\frac{1}{8}\)
\(=\frac{-5}{8}.\left(\frac{5}{12}+\frac{7}{12}\right)+\frac{17}{8}\)
\(=\frac{-5}{8}.1+\frac{17}{8}\)
\(=\frac{3}{2}\)
Câu 2: a, \(x-\frac{2}{5}=0,24\)
\(x-0,4=0,24\)
\(x=0,24+0,4\)
\(\Rightarrow x=0,64\left(\frac{16}{25}\right)\)
b,\(\frac{2}{3}.x+\frac{1}{12}=\frac{1}{10}\)
\(\frac{2}{3}.x=\frac{1}{10}-\frac{1}{12}\)
\(\frac{2}{3}.x=\frac{1}{60}\)
\(x=\frac{1}{60}:\frac{2}{3}\)
\(\Rightarrow x=\frac{1}{40}\)
c, \(\left(3\frac{1}{2}-2x\right).1\frac{1}{3}=7\frac{1}{3}\)
\(\frac{7}{2}-2x=\frac{22}{3}:\frac{4}{3}\)
\(\frac{7}{2}-2x=\frac{11}{2}\)
\(2x=\frac{7}{2}-\frac{11}{2}\)
\(2x=-2\)
\(\Rightarrow x=-2:2\)
\(x=-1\)
(3,5 + 2x).2 2/3 = 5 1/3 => (3,5 + 2x).8/3 = 16/3 => 3,5 + 2x = 16/3 : 8/3 = 2/3 => 21/6 + 2x = 4/6 => 2x = 4/6 - 21/6 = -17/6 => x = -17/6 : 2 = -17/12
Tìm x:
b) 1/3.x+2/5.(x-1)=0
\(<=> \dfrac{1}{3} .x +\dfrac{2}{5}x - \dfrac{2}{5} =0\)
\(<=> \dfrac{11}{15}x = \dfrac{2}{5}\)
\(<=> x= \dfrac{6}{11}\)
Vậy \( x= \dfrac{6}{11}\)
c) (2x-3).(6-2x)=0
\(<=> \begin{cases}
2x-3=0 \\
6-2x=0
\end{cases}\) \(<=> \begin{cases}
2x=3 \\
-2x=-6
\end{cases}\) \(<=>\begin{cases}
x=\dfrac{3}{2} \\
x=3
\end{cases}\)
Vậy \(x=( \dfrac{3}{2} ; 3)\)
d) -2/3-1/3.(2x-5)= 3/2
\(<=> 2x-5= \dfrac{5}{2}\)
\(<=> 2x= \dfrac{15}{2}\)
\(<=> x= \dfrac{15}{4}\)
Vậy \(x= \dfrac{15}{4}\)
f) 1/3.x-1/2=4 và 1/2 (Hỗn số ý '^')
\(<=> \dfrac{1}{3} x -\dfrac{1}{2} = \dfrac{9}{2}\)
\(<=> \dfrac{1}{3}x =5\)
\(<=> x= 15\)
Vậy \(x= 15\)
\(\left(2x-\frac{1}{3}\right)\left(3x+\frac{1}{2}\right)=0\)
\(=>\orbr{\begin{cases}2x-\frac{1}{3}=0\\3x+\frac{1}{2}=0\end{cases}}\)
\(=>\orbr{\begin{cases}2x=\frac{1}{3}\\3x=\frac{-1}{2}\end{cases}}\)
\(=>\orbr{\begin{cases}x=\frac{1}{6}\\x=\frac{-1}{6}\end{cases}}\)
\(\left(3\frac{1}{2}+2x\right).2\frac{2}{3}=5\frac{1}{3}\)
\(\left(\frac{7}{2}+2x\right).\frac{8}{3}=\frac{16}{3}\)
\(\frac{7}{2}+2x=\frac{16}{3}:\frac{8}{3}\)
\(\frac{7}{2}+2x=\frac{16}{3}.\frac{3}{8}\)
\(\frac{7}{2}+2x=2\)
\(2x=2-\frac{7}{2}\)
\(2x=-\frac{3}{2}\)
\(x=-\frac{3}{2}:2\)
\(x=-\frac{3}{2}.\frac{1}{2}\)
\(x=-\frac{3}{4}\)
\(\left(3\frac{1}{2}+2x\right).2\frac{2}{3}=5\frac{1}{3}\)
\(\Rightarrow\left(\frac{7}{2}+2x\right).\frac{8}{3}=\frac{16}{3}\)
\(\Rightarrow\frac{7}{2}+2x=\frac{16}{3}:\frac{8}{3}\)
\(\Rightarrow\frac{7}{2}+2x=\frac{16}{3}.\frac{3}{8}\)
\(\Rightarrow\frac{7}{2}+2x=2\)
\(\Rightarrow2x=2-\frac{7}{2}\)
\(\Rightarrow2x=\frac{4}{2}-\frac{7}{2}\)
\(\Rightarrow2x=-\frac{3}{2}\)
\(\Rightarrow x=\left(-\frac{3}{2}\right):2\)
\(\Rightarrow x=\left(-\frac{3}{2}\right).\frac{1}{2}\)
\(\Rightarrow x=\frac{-3}{4}\)